Comparing levels of self-perceieved and actual communicative competence in English of Filipino grade 12 students in Metro Manila - Salazar, Maria Rhodora S. 1962-; Pernia, Elena E.; University of the Philippines Diliman. College of Mass Communication (Quezon City : College of Mass Communications, University of the Philippines Diliman, 2019.)
"Is there a difference between a person's self-perceived and actual communicative competence in English? Using a framework derived from Canale and Swain's Communicative Competence as well as Bachman and Palmer's Model of Communicative Competence, the research follows a quantitative approach to compare Metro Manila student's self-perceived and actual communicative competence in English, ie. performance in terms of communication roles, communication modes, communication strategies, and communication skills. These Filipino students' level of self-perceived and actual English communicative competence were compared according to their sex, income class, type of school attended, foreign travel experience, movie preference, and use of English at home. First, 185 respondents enrolled in Grade 12 were subjected to a survey questionnaire to find out their self-reported levels of communicative competence in English. Then, these same respondents were asked to answer the Test of English for International Communication (TOEIC) to assess their actual level of communicative competence in English. Data showed that the respondents see themselves as having better English skills than they actually posses, suggesting that confidence in one's ability in using a language is a positive element in building communication skills. The role of English as a global language of communication and its status as the working language of the ASEAN region have important implications for language education particularly in the Philippines. It is hoped that findings of this study provide the impetus toward the further development of English communicative competence in the Philippines, which has been waning in the recent years. The study concludes with specific recommendations for educators and policy makers to improve "teaching-learning effectiveness" for students in basic education."
Vita.
Thesis (Master of Arts in Communication)--University of the Philippines Diliman
Includes bibliographical references (pages 170-177).
Keywords: Communicative competence -- Philippines -- Metro Manila; English language -- Study and teaching (Secondary) -- Philippines -- Metro Manila